2019
DOI: 10.1007/s12020-019-02052-2
|View full text |Cite
|
Sign up to set email alerts
|

T4 + T3 combination therapy: any progress?

Abstract: Guidelines on T4 + T3 combination therapy were published in 2012. This review investigates whether the issue is better understood 7 years later. Dissatisfaction with the outcome of T4 monotherapy remains high. Persistent symptoms consist mostly of fatigue, weight gain, problems with memory and thinking and mood disturbances. T4 monotherapy is associated with low serum T3 levels, which often require TSH-suppressive doses of L-T4 for normalization. Peripheral tissue thyroid function tests during T4 treatment ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…Second, it is not clear whether “pulsatile” T3 levels during LT3 dosing have different effects on T3 action, in both pituitary and elsewhere. There are little data to inform this, but if “pulsatile” T3 has a greater effect on TSH suppression than a similar amount of T3 distributed evenly throughout the 24-h period, this could explain why the trials that showed a preference for LT3 in combination with LT4 were generally associated with lower, sometimes “subnormal” TSH levels [89]. In support of this, it is noted that in the Thyroid Epidemiology, Audit, and Research (TEARS) retrospective review of patients in Scotland, of 400 individuals using LT3, compared with 33,995 patients taking LT4, no excess of cardiovascular disease including atrial fibrillation was noted despite TSH levels being substantially lower in LT3 users (1.07 vs. 2.08 mIU/L, p < 0.001), suggesting that a lower TSH on LT3 therapy does not necessarily reflect over-replacement [38].…”
Section: Results: Topics Summaries Summary Statements and Consensusmentioning
confidence: 99%
“…Second, it is not clear whether “pulsatile” T3 levels during LT3 dosing have different effects on T3 action, in both pituitary and elsewhere. There are little data to inform this, but if “pulsatile” T3 has a greater effect on TSH suppression than a similar amount of T3 distributed evenly throughout the 24-h period, this could explain why the trials that showed a preference for LT3 in combination with LT4 were generally associated with lower, sometimes “subnormal” TSH levels [89]. In support of this, it is noted that in the Thyroid Epidemiology, Audit, and Research (TEARS) retrospective review of patients in Scotland, of 400 individuals using LT3, compared with 33,995 patients taking LT4, no excess of cardiovascular disease including atrial fibrillation was noted despite TSH levels being substantially lower in LT3 users (1.07 vs. 2.08 mIU/L, p < 0.001), suggesting that a lower TSH on LT3 therapy does not necessarily reflect over-replacement [38].…”
Section: Results: Topics Summaries Summary Statements and Consensusmentioning
confidence: 99%
“…), most of the investigators felt that the potential benefits for QoL did not provide a clear clinical rationale in favor of LT4 + LT3. However, the frequent patient preference for LT4 + LT3 (for as-yet unknown reasons) [ 51 ] reinforces Wiersinga’s suggestion that robust clinical trials in selected patient subpopulations are essential for making progress in this field [ 99 ].…”
Section: Discussionmentioning
confidence: 97%
“…From the early 2000s onwards, it has often been suggested that patients who experience persistent symptoms of hypothyroidism and/or poor QoL during treatment with LT4 alone may benefit from LT4 + LT3 combination treatment. However, almost 20 years later, the merits and limitations of this strategy are still subject to debate [ 97 , 98 , 99 ].…”
Section: Quality Of Life In Patients Treated For Hypothyroidismmentioning
confidence: 99%
“…However, several randomized controlled studies have failed to demonstrate better patient outcomes with L‐T4 + LT3 combination therapy compared to L‐T4 alone 33,34 and a single randomized controlled trial found no difference between DTE and L‐T4 treatment 35 . Although L‐T4 + L‐T3 treatment in trials may not have been optimized, 36 it seems that other factors may be of importance in determining satisfaction and QOL associated with treatment of hypothyroidism. It is therefore worth exploring these as they might provide new avenues for improving patient satisfaction and QOL.…”
Section: Discussionmentioning
confidence: 99%